2014
DOI: 10.3390/ma7032273
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Molecular Conformations and Microstructure on the Optoelectronic Properties of Conjugated Polymers

Abstract: It is increasingly obvious that the molecular conformations and the long-range arrangement that conjugated polymers can adopt under various experimental conditions in bulk, solutions or thin films, significantly impact their resulting optoelectronic properties. As a consequence, the functionalities and efficiencies of resulting organic devices, such as field-effect transistors, light-emitting diodes, or photovoltaic cells, also dramatically change due to the close structure/property relationship. A range of st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
79
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(82 citation statements)
references
References 174 publications
(224 reference statements)
2
79
0
1
Order By: Relevance
“…As the two materials have different surface tensions and surface functions, similarly to the work on PFETs [36], different crystallite orientations should be expected for active layers in regular and inverted device architectures. In fact, in PSCs prepared with Naphtho[1,2-c:5,6-c ]bis [1,2,5]thiadiazole based p-type polymer (PNTz4T): [6,6]-phenyl-C 71 -butyric acid methyl ester (PC 71 BM) blend solutions, the active layer solution has different wetting properties on PEDOT:PSS and ZnO [25]. Consequently, a different amount of face-on and edge-on crystallites is generated in the thin blend films deposited on the ITO substrates with the two different coatings.…”
Section: Molecular Orientation Induced By Materials Interaction Durinmentioning
confidence: 99%
See 2 more Smart Citations
“…As the two materials have different surface tensions and surface functions, similarly to the work on PFETs [36], different crystallite orientations should be expected for active layers in regular and inverted device architectures. In fact, in PSCs prepared with Naphtho[1,2-c:5,6-c ]bis [1,2,5]thiadiazole based p-type polymer (PNTz4T): [6,6]-phenyl-C 71 -butyric acid methyl ester (PC 71 BM) blend solutions, the active layer solution has different wetting properties on PEDOT:PSS and ZnO [25]. Consequently, a different amount of face-on and edge-on crystallites is generated in the thin blend films deposited on the ITO substrates with the two different coatings.…”
Section: Molecular Orientation Induced By Materials Interaction Durinmentioning
confidence: 99%
“…However, depending on which process conditions and deposition process are employed, the nanoscale morphology of the thin conjugated polymer films can vary enormously [4]. A large number of scientific papers have been published on the effect of the process conditions over the resulting morphology, trying to understand the correlation between morphology and performances [5][6][7]. In fact, understanding these correlations from both theoretical and experimental points of view represents a major achievement to increase the performances of conjugated polymer devices such as polymer solar cells (PSCs), polymer light-emitting devices (PLEDs), or polymer field-effect transistors (PFETs).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[21(b)] their overriding importance, new methods to manipulate them are continuously being pursued. [4] It has been proven that, efficient and rapid migration of excitation and charges through CPs material could be reached by films having ordered structures from the nano to macroscale. [5] Generally, the molecular self-assembly (Sa) in solution or in melt, is an elegant path to achieve reproducible materials structuring at the nanometer scale.…”
Section: Introductionmentioning
confidence: 99%
“…The device performance is determined by the structural organization of the interpenetrating network, interface energy and self-assembly of active layer composites. 90,91 Theoretical studies and experimental results of organic photovoltaic devices have shown that P3HT chains can selfassemble to wrap around the carbon based nanostructures and change the conjugation length of the P3HT to modify the device charge transfer properties. 91,92 It is proposed that the large interface area provided in the open ended worm like structure could increase the interconnectivity to the P3HT chains and thus, alter the charge transfer properties in the active layer composite.…”
Section: 51mentioning
confidence: 99%